2010
DOI: 10.1007/s10508-010-9682-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Protection Behavior in HIV-Positive Gay Men: Testing a Modified Information-Motivation-Behavioral Skills Model

Abstract: This study on determinants of sexual protection behavior among HIV-positive gay men used the empirically tested information-motivation-behavioral skills (IMB) model. HIV-specific variables were added to the model to determine factors decisive for condom use with steady and casual partners. Data were collected using an anonymous, standardized self-administered questionnaire. Study participants were recruited at HIV outpatient clinics associated with the Eurosupport Study Group and the Swiss HIV Cohort Study. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Trimming or modifying our TB IC IMB models by removing the information inputs resulted in a more accurate characterization of implementation. This finding is in line with some IMB studies that found that information was not strongly predictive of regular safer sexual practices among various populations [13][14][15]33]. A possible reason for the inconsistent associations of information in our study is that the generally high information levels of our sample may have caused a ceiling effect (i.e., knowledge was high enough to no longer have a measurable effect on implementation frequency).…”
Section: Tb Ic Imb Modelingsupporting
confidence: 84%
See 1 more Smart Citation
“…Trimming or modifying our TB IC IMB models by removing the information inputs resulted in a more accurate characterization of implementation. This finding is in line with some IMB studies that found that information was not strongly predictive of regular safer sexual practices among various populations [13][14][15]33]. A possible reason for the inconsistent associations of information in our study is that the generally high information levels of our sample may have caused a ceiling effect (i.e., knowledge was high enough to no longer have a measurable effect on implementation frequency).…”
Section: Tb Ic Imb Modelingsupporting
confidence: 84%
“…1) states that well-informed, motivated individuals develop necessary behavioral skills, which lead to effective practices [12]. This model has been useful in characterizing and enhancing HIV risk reduction behaviors [13][14][15], antiretroviral therapy adherence [16][17][18], and diet and exercise [19]. We hypothesized that the IMB model could characterize HCW TB IC adherence and inform IC enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…However, HIV‐related information was not a significant predictor of CAS. Other researchers also have failed to find a significant relation between HIV knowledge and CAS (e.g., Newcomb & Mustanski, ; Nostlinger et al, ). It is likely, though, that HIV‐related knowledge has an effect on sexual behaviors through impacting behavioral skills (e.g., discussing safer sex with partners) instead of solely a direct effect (Fisher, Fisher, Williams, & Malloy, ).…”
Section: Psychosocial Models Predicting Hiv Risk Behaviors and Hiv Acmentioning
confidence: 96%
“…The intervention, originally developed in the U.S., was chosen for adaptation for use in Russia for two reasons. First, it is based on the Information-Motivation-Behavioral Skills (IMB) model (Fisher JD & Fisher WA, 1992, 2000), a well-validated theoretical model for predicting health promotion behaviors (including HIV prevention behaviors) and has been used to develop effective behavioral interventions for use throughout the world (Ali SS & Manongi RR, 2010; Amico KR et al , 2009; Ferrer RA et al , 2010; Malow RM et al , 2009; Nostlinger C et al , 2011; Osborn CY et al , 2010c; Osborn CY & Egede LE, 2010a; Osborn CY et al , 2010b; Peltzer KK et al , 2011; Shattuck D et al , 2011; Tipwareerom W et al , 2011; Zhang H et al , 2011); hence, it has proven applicability across many populations and cultures. The IMB model states that HIV information (i.e., knowledge about transmission, risk, and prevention), motivation to engage in HIV preventive behaviors, and behavioral skills are necessary prerequisites to engaging in such behaviors.…”
Section: Introductionmentioning
confidence: 99%